The myth of perfection: the image of TV-Globo newscasters - Hagen, Sean (Brazilian journalism research, 2005)
The focus of this article is on the mythical image of perfection of the newscasters of the Jornal Nacional – Globo Television Network – constructed by the Brazilian media. Both as soft as well as hard news in magazines, newspapers and information sites, Fátima Bernardes and William Bonner are structured as a couple completely fulﬁ lled in the profession, in love and in family relationships. This reading is possible due to the overlapping of journalism and mythical thought. Using discourse analysis concepts as a support, we have analyzed 168 texts between 1998 and 2004, pointing out how the media have constructed this image and what meanings they have mobilized on attributing to the couple a special place in the pantheon of mass culture celebrities. Three distinct formations stand out: a) love, fame and beauty; b) talent and professional success; c) family and morals. More than just journalists, the newscasters are portrayed as stars with impeccable morals, diﬀ erent from the vulgar celebrities present in the current media.